2014
DOI: 10.1061/(asce)me.1943-5479.0000204
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Leadership as Enablers of Innovation in Construction: Case Study

Abstract: Wireless sensor networks have become incredibly popular due to the Internet of Things' (IoT) rapid development. IoT routing is the basis for the efficient operation of the perception-layer network. As a popular type of machine learning, reinforcement learning techniques have gained significant attention due to their successful application in the field of network communication. In the traditional Routing Protocol for lowpower and Lossy Networks (RPL) protocol, to solve the fairness of control message transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 31 publications
7
79
0
3
Order By: Relevance
“…Previous studies indicated that leadership has been be considered as an important precursor of organizational performance, especially at the individual level but also at the organizational level [26,91]. The goal of this study was to extend the research towards construction projects and to provide an empirical test for the ambidexterity theory of leadership and culture in project management field.…”
Section: The Direct Effects Of Ambidextrous Leadership On Project Permentioning
confidence: 99%
“…Previous studies indicated that leadership has been be considered as an important precursor of organizational performance, especially at the individual level but also at the organizational level [26,91]. The goal of this study was to extend the research towards construction projects and to provide an empirical test for the ambidexterity theory of leadership and culture in project management field.…”
Section: The Direct Effects Of Ambidextrous Leadership On Project Permentioning
confidence: 99%
“…Because knowledge sharing is an enabler of innovation, the leadership style that promotes an open communication of innovative ideas and approaches is essential for organizational innovation [20]. Transformational leaders that nurture the intrinsic development of employees by considering their participation and ideas are essential for an organization [9].…”
Section: The Differentiation Of the Two Leadership Stylesmentioning
confidence: 99%
“…Nam and Tatum (1997) found out that to foster innovation, there must be implicit vertical integration. Ozorhon et al (2014) also conclude that integration and leadership are two important enablers of innovation in construction.…”
Section: The Characteristics Of Construction Innovationmentioning
confidence: 99%
“…Literature exploring the process of construction innovation once considered innovation is the responsibility of individual firms (Gann & Salter, 2000;Ozorhon et al, 2014). However, in the recent era, researchers increasingly emphasize the importance of interfirm cooperation relationships and networks in innovation projects (Holmen, Pedersen, & Torvatn, 2005;Rothwell, 1992;Slaughter, 1998).…”
Section: The Characteristics Of Construction Innovationmentioning
confidence: 99%
See 1 more Smart Citation